2004
DOI: 10.1590/s1516-635x2004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broilers fed diets with different dietary electrolyte balance under summer conditions

Abstract: The aim of this study was to compare performance and carcass characteristics of broilers fed diets with different Dietary Electrolyte balances (DEB) during the summer season. A total of 1,280 one-day-old Ross sexed chicks were distributed in 32 experimental units according to a randomized block design in a 4x2 factorial arrangement (4 levels and 2 sexes) and 4 replicates per treatment (40 birds per replicate). Feed program consisted of 3 phases (1-21, 22-42, 43-49 days of age). Experimental diets were formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
3
9
0
6
Order By: Relevance
“…In an experiment reported by Borgatti et al (2004), a high weight gain was found at 1.8 g·Na + , 12.2 g·K + and 2.2 g·Cl · kg -1 of diet and at a DEB value of 330. In our experiment the highest BWG values, the largest FI and the best FCR in the first feeding period were observed in chickens fed diets containing higher K + (12.2 and 12.7 g·kg -1 ), Na + L and Na + A (1.22 and 1.68 g·kg -1 ) content and with DEB values from 329 to 349.…”
Section: Discussionmentioning
confidence: 86%
“…In an experiment reported by Borgatti et al (2004), a high weight gain was found at 1.8 g·Na + , 12.2 g·K + and 2.2 g·Cl · kg -1 of diet and at a DEB value of 330. In our experiment the highest BWG values, the largest FI and the best FCR in the first feeding period were observed in chickens fed diets containing higher K + (12.2 and 12.7 g·kg -1 ), Na + L and Na + A (1.22 and 1.68 g·kg -1 ) content and with DEB values from 329 to 349.…”
Section: Discussionmentioning
confidence: 86%
“…Feeding diets containing higher potassium content (1.22% and 1.27%) with dietary electrolyte balance (DEB) values from 329 to 349, decreased broiler chickens performance (Koreleski et al 2010) and inclusion of 25% and 50% more than basal diet to male turkey diets reduced weight gain but had no effect on FCR (Reece et al 2000). Nevertheless, in other experiment broiler chickens fed diet containing 0.18% sodium, 1.22% potassium and 0.22% chlorine with DEB value of 330, achieved high weight gain (Borgatti et al 2004). However, in our experiment, potassium and sodium levels were not more than 0.95 and 0.17%, respectively, and it was suggested that when dietary potassium was 1.01%, sodium is not needed more than 0.20% for 0-21d chickens (Murakami et al 1997).…”
Section: Growth Performance and Immune Responsementioning
confidence: 96%
“…In addition, EB values in the diet change with animal species, production category, and age, as well as with the intensity and duration of heat stress. Experiments carried out with broilers, commercial layers, and broiler breeders determined different dietary EB for these categories of chickens (Junqueira et al, 2000, Borgatti et al, 2004 and for different environmental temperatures. Quails originate from hot regions (McIlvaine, 2000), and therefore, probably are more resistant to heat stress than chickens.…”
Section: Introductionmentioning
confidence: 99%